AUDIENCE RECEPTION ANALYSIS OF ELSA’S LEADERSHIP IN DISNEY’S FROZEN 2 - Yunia Anindya (LITERA KULTURA : Journal of Literary and Cultural Studies, 2022)
This study explores Elsa’s character that portrays women’s leadership from the audience’s perspectives by using an audience reception theory by Stuart Hall to analyze the data collected. There are three positions by using Stuart Hall’s Encoding – Decoding concepts, such as dominant, negotiated, and oppositional positions. This study shows that almost all respondents are in dominant positions, which agree with Frozen 2’s ideology of Elsa’s character regarding women’s leadership. This study can explore the study that focuses on women’s leadership. The main part of the research includes audience reception since the audience reception approach could gain new insight from many different views. Keywords: audience reception, women’s leadership, Disney